The Impact of Visual Impairment on Perceived School Climate - Benjamin P. Schade; Karen H Larwin (International Journal of Evaluation and Research in Education (IJERE), 2015)
The current investigation examines whether visual impairment has an impact on a student’s perception of the school climate. Using a large national sample of high school students, perceptions were examined for students with vision impairment relative to students with no visual impairments. Three factors were examined: self-reported level of happiness, perception of a positive school climate, and negative school affect.  Results revealed no differences for the seeing and visually impaired students on self-reported happiness and perception of a positive school climate factors, however significant differences were found on the negative school affect factor. Additionally, gender was significantly related to the negative school affect factor.